PERAN DINAS KESEHATAN DALAM MENANGGULANGI GIZI BURUK ANAK DI KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT - Indra Slamet Gumelar (Jurnal Caraka Prabu, 2018)
The title of this research is "The Role of the Health Office in Tackling Child Malnutrition in Ngamprah District, West Bandung Regency". The problem in this research is not yet optimal implementation of the Health Office in Overcoming Malnutrition in Children in Ngamprah District, West Bandung Regency. The research method that researchers use is descriptive research methods with a qualitative approach. The technique of determining the informants used was purposive sampling technique. The results showed that in carrying out its duties and functions, the health office, the Health Office had implemented a sufficiently optimal role seen from the six indicators of success in overcoming malnutrition, namely: All Posyandu carry out weighing operations at least once a month All toddlers are weighed, All cases of malnutrition are referred to the Puskemas Nursing or Home Sick, all cases of malnutrition are treated at the health center. Nursing or hospitalization is handled according to the management of malnutrition. All post-treatment malnourished toddlers receive assistance.